tmRNA-mediated trans-translation as the major ribosome rescue system in a bacterial cell - Himeno, Hyouta; Kurita, Daisuke; Muto, Akira (Frontiers in Genetics, 2014)
tmRNA (transfer messenger RNA; also known as 10Sa RNA or SsrA RNA) is a small RNA molecule that is conserved among bacteria. It has structural and functional similarities to tRNA: it has an upper half of the tRNA-like structure, its 5’ end is processed by RNase P, it has typical tRNA-specific base modifications, it is aminoacylated with alanine, it binds to EF-Tu after aminoacylation and it enters the ribosome with EF-Tu and GTP. However, tmRNA lacks an anticodon, and instead it has a coding sequence for a short peptide called tag-peptide. An elaborate interplay of actions of tmRNA as both tRNA and mRNA with the help of a tmRNA-binding protein, SmpB, facilitates trans-translation, which produces a single polypeptide from two mRNA molecules. Initially alanyl-tmRNA in complex with EF-Tu and SmpB enters the vacant A-site of the stalled ribosome like aminoacyl-tRNA but without a codon-anticodon interaction, and subsequently truncated mRNA is replaced with the tag-encoding region of tmRNA. During these processes, not only tmRNA but also SmpB structurally and functionally mimics both tRNA and mRNA. Thus trans-translation rescues the stalled ribosome, thereby allowing recycling of the ribosome. Since the tag-peptide serves as a target of AAA+ proteases, the trans-translation products are preferentially degraded so that they do not accumulate in the cell. Although alternative rescue systems have recently been revealed, trans-translation is the only system that universally exists in bacteria. Furthermore, it is unique in that it employs a small RNA and that it prevents accumulation of nonfunctional proteins from truncated mRNA in the cell. It might play the major role in rescuing the stalled translation in the bacterial cell.